Dopamine prevents impairment of autoregulation after traumatic brain injury in the newborn pig through inhibition of Up-regulation of endothelin-1 and extracellular signal-regulated kinase mitogen-activated protein kinase - Armstead, William M; Riley, John; Vavilala, Monica S (Pediatric critical care medicine, 2013)
Traumatic brain injury contributes to morbidity in children and boys are disproportionately represented. Autoregulation is impaired more in male compared with female piglets after traumatic brain injury through sex-dependent up-regulation of the spasmogen endothelin-1 and extracellular signal-regulated kinase (ERK) mitogen-activated protein kinase (MAPK), a family of three kinases: ERK, p38, and JNK). Elevation of mean arterial pressure leading to increased cerebral perfusion pressure via phenylephrine improves impairment of autoregulation after traumatic brain injury in female but not male piglets through modulation of endothelin-1 and ERK MAPK up-regulation, blocked in females, but aggravated in males. We hypothesized that pressor choice to elevate cerebral perfusion pressure is important in improving cerebral hemodynamics after traumatic brain injury and that dopamine will prevent impairment of autoregulation in both male and female piglets through blockade of endothelin-1 and ERK MAPK. Prospective, randomized animal study. University laboratory. Newborn (1-5 days old) pigs. Cerebral perfusion pressure and pial artery diameter were determined before and after lateral fluid percussion brain injury was produced in piglets equipped with a closed cranial window. Dopamine (15 µg/kg/min IV) was administered 30 mins post fluid percussion injury. Cerebrospinal fluid ERK MAPK was determined by enzyme-linked immunosorbent assay. Dopamine increased cerebral perfusion pressure equivalently in both sexes and prevented sex-dependent reductions in pial artery diameter after fluid percussion injury. Loss of pial artery dilation during hypotension was greater in male than in female piglets after fluid percussion injury, but dopamine prevented such impairment equivalently in both sexes post injury. endothelin-1 and ERK MAPK release was greater in male compared to female piglets after fluid percussion injury, but dopamine also blocked their up-regulation equivalently in male and female piglets after fluid percussion injury. These data indicate that dopamine is protective of autoregulation after fluid percussion injury in both sexes. These observations advocate for the consideration of development of sex based therapies for treatment of hemodynamic sequalae of pediatric traumatic brain injury.